Depletion of Survivin suppresses docetaxel-induced apoptosis in HeLa cells by facilitating mitotic slippage - Teng-Long Han (Nature Portfolio, 2021)
Abstract The anticancer effects of taxanes are attributed to the induction of mitotic arrest through activation of the spindle assembly checkpoint. Cell death following extended mitotic arrest is mediated by the intrinsic apoptosis pathway. Accordingly, factors that influence the robustness of mitotic arrest or disrupt the apoptotic machinery confer drug resistance. Survivin is an inhibitor of apoptosis protein. Its overexpression is associated with chemoresistance, and its targeting leads to drug sensitization. However, Survivin also acts specifically in the spindle assembly checkpoint response to taxanes. Hence, the failure of Survivin-depleted cells to arrest in mitosis may lead to taxane resistance. Here we show that Survivin depletion protects HeLa cells against docetaxel-induced apoptosis by facilitating mitotic slippage. However, Survivin depletion does not promote clonogenic survival of tumor cells but increases the level of cellular senescence induced by docetaxel. Moreover, lentiviral overexpression of Survivin does not provide protection against docetaxel or cisplatin treatment, in contrast to the anti-apoptotic Bcl-xL or Bcl-2. Our findings suggest that targeting Survivin may influence the cell response to docetaxel by driving the cells through aberrant mitotic progression, rather than directly sensitizing cells to apoptosis.